The effectiveness of the role of the school committee in SD Negeri 1 Maibua - Jepri Utomo; Inayatul Mutmainnah (Balai Diklat Keagamaan Ambon, 2022)
This study aims to describe the effectiveness of the role of the School Committee in SD Negeri 1 Maibua. This study uses a descriptive type survey method. The population is heterogeneous, and the sampling was done by purposive sampling. Types of data in the form of qualitative and quantitative. The data sources are primary and secondary. Three data collection techniques were used, namely: questionnaires, interviews, and observations. The data that has been collected is then analyzed descriptively qualitatively, namely by grouping the data by categorization and then each category is given a percentage weight according to the existing events. The findings show that the role of the School Committee in SD Negeri 1 Maibua is quite effective.